Practices and Perception of Community Pharmacists Towards Antimicrobial Stewardship in Iraq - Dheyaa Jabbar Kadhim; Ammar Fadhil Shanan (Iraqi Journal of Pharmaceutical Sciences, 2025)
Abstract The development of antimicrobial resistance (AMR) is related mostly to their use, overuse, or misuse. Antimicrobial stewardship (AMS) refers to the interventions designed to measure and improve the appropriate use of antimicrobials by promoting the selection of the optimal antimicrobial drug, dose, duration of therapy, and route of administration. Community pharmacists are key health-care professionals for any AMS programs due to their role in dispensing of antimicrobials. This study aimed to evaluate the practices and perception of Iraqi community pharmacists regarding AMS. The present study was a cross-sectional online survey study that was conducted anonymously during two months’ period (July-to-August 2021) on community pharmacists using a convenience sampling technique. The study recruited 210 pharmacists with average age of (29.55 ±6.45 years) and more than half (50.95%) were men. The average years of pharmacist experience were (5.45±5.15 years). Most of them lived in Baghdad (61.9%). Regarding practices of community pharmacists towards AMS, the results of the present study revealed positive practices of community pharmacists towards AMS (the median score was 42 which above the average). However; about (39.0%) of community pharmacists agreed that they dispense antibiotics without prescription. The majority of pharmacists (80%) agreed that they recommend medicines other than antimicrobials for minor conditions. In addition, about (77%) disagreed that they dispense antibiotics for a longer duration than prescribed by the physicians. Regarding the perception of community pharmacists towards AMS, the results of the present study revealed neutral perception (the median score was 30 which equal to the average). More than three quarter of respondents (about 78%) agreed that they keep in mind side effects while dispensing antibiotics. In this study, the majority of community pharmacists (about 87%) agreed that most of population self-medicate with antibiotics. Finally, results of the current study show that none of the sociodemographic characteristic of the participants had a significant effect on practices and perception of community pharmacists towards AMS. In conclusion, community pharmacists in Iraq, have neutral perception regarding AMS and they are practicing it well. But there are some gaps in their practices that must be addressed, such dispensing antibiotics without a prescription and dispensing antibiotics for a longer duration than prescribed.